The Effect of Electroacupuncture on the Expression of p53 mRNA in Newborn Rats following Hypoxic-ischemic Encephalopathy - Zhang, Hui; Li, Meng; Sun, Qing (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
Aim: To explore the neuroprotective effects of electroacupuncture on the expression of p53 in newborn rats following hypoxic-ischemic encephalopathy (HIE).Method: The hypoxic-ischemic models were made in new-born SD rats aged 7 days by colligating bilateral common carotid artery(CCA). All rats were randomly divided into sham-surgery group, model group and electroacupuncture group (EA), and the successfully established rat models were subdivided in to 1d, 3d, 7d, 21d,three time-phases. The changes of morphology in the injured cortex were observed by pathology; the real-time PCR was used to determine the expression level of P53mRNA in the injured cortex. Results: HE and pathological staining indicated that the nerve cells are arranged in order, the structure is normal, and the cell outline and the nucleus are clear at 21d in EA group. The expression of p53mRNA in 1d, 3d, 7d, 21d, four points in EA group were significantly increased than those in model group (P<0.05). Conclusion: EA plays a neuroprotective effect through promoting the expression of p53mRNA in hypoxic-ischemic brain tissuein rats.